Extractive distillation for CO2–ethane azeotrope separation - Lastari, Fonny; Pareek, Vishnu; Trebble, Mark; Tade, Moses; Chinn, D.; Tsai, N.; Chan, K. (Elsevier BV, 2012)
The separation of the CO2–ethane azeotrope using the hydrocarbon solvents through an extractive distillation process was simulated with the HYSYS 2004.2 software platform. The objective was to examine the optimum solvent amount and composition as well as the optimum feed and solvent location in terms of the overall energy demand. The rigorous simulation results showed that the ratio of the optimum solvent to the minimum solvent amount was in the range of 1.053–1.064 for C4 and C5 solvents in treating the equimolar CO2–ethane mixture. It was also observed that C4 and C5 solvents were more efficient than C3 solvent due to the lower solvent amount and associated energy demand. The feed and solvent inlet stages have significant effect on the overall energy demand of the column. The best solvent inlet stage is generally near the top of the column, however, an increased solvent loss was observed.